Comparative analysis on excerpts about Desht-i Kypchak from Al-‘Umari’s and Al-Kalkashandi’s essays (Journal of Oriental Studies, 2018)
In this article, comparative analysis on excerpts from Al-‘Umari’s essay “Masalik al-absar fi mamalikal-amsar” and Al-Kalkashandi’s “Subh al-a‘sha fi kitabat al-insha” was being considered. These worksare the important sources on the history of Desht-i Kypchak. In the excerpts the state Desht-i Kypchak, itsgeography, way of life, economy, the military order of the Kypchaks and the social status of the Kypchakwomen are described.